PENGARUH MODEL PEMBELAJARAN KOOPERATIF TEAM GAMES TOURNAMENT (TGT) BERBANTUAN APLIKASI KAHOOT TERHADAP KEMAHIRAN MEMBACA TEKS PUISI PADA SISWA KELAS VIII SMP NEGERI 6 BINTAN TIMUR TAHUN PELAJARAN 2024/2025 - Julianti Siahaan, Sonya; Leo Shanty, Isnaini; Lolita, Asri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the effect of the Team Games Tournament (TGT) learning model assisted by the Kahoot application on the poetry reading skills of eighth-grade students at SMP Negeri 6 Bintan Timur with a population of 73 students and a sample of 44 students in Indonesian language learning. This study is quantitative descriptive. This study used an experimental method with a one-group pretest-posttest design. The data collection technique was an objective test. Based on the normality test, the research data showed that the data were normally distributed. The t-test results showed a significance value of 0.000 < 0.05, so it can be stated that the hypothesis is accepted. This means that there is an effect of the Team Games Tournament (TGT) cooperative learning model assisted by the Kahoot application on the poetry reading skills of eighth-grade students at SMP Negeri 6 Bintan Timur in the 2024/2025 academic year.